2005
DOI: 10.1364/ol.30.001923
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a passive subpicostrain fiber strain sensor

Abstract: Abstract-We demonstrate a fiber Fabry-Perot (FFP) sensor capable of detecting sub-picostrain signals, from 100 Hz and extending beyond 100 kHz, using the Pound-Drever-Hall frequency locking technique. A low power diode laser at 1550 nm is locked to a free-space reference cavity to suppress its free-running frequency noise, thereby stabilizing the laser. The stabilized laser is then used to interrogate a FFP where the PDH error signal yields the instantaneous fiber strain.Index Terms-fiber sensor, modulation, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 12 publications
(13 reference statements)
0
51
1
Order By: Relevance
“…In many fiber-based systems, such as interferometric fiber-optic sensors [1][2][3][4] , fiber lasers [5][6][7] , and fiber-delay-line stabilized lasers 8 , the fundamental resolution or frequency stability is limited by the intrinsic thermal noise inside optical fibers. Thus, an experimental and theoretical understanding of the thermal noise in optical fibers is important.…”
mentioning
confidence: 99%
“…In many fiber-based systems, such as interferometric fiber-optic sensors [1][2][3][4] , fiber lasers [5][6][7] , and fiber-delay-line stabilized lasers 8 , the fundamental resolution or frequency stability is limited by the intrinsic thermal noise inside optical fibers. Thus, an experimental and theoretical understanding of the thermal noise in optical fibers is important.…”
mentioning
confidence: 99%
“…This result leads us to conlcude that the cross sectional area of a POF is equal with the intensity of that POF. That is, the light energy distribution is 1 Il-Bum Kwon 1 Chi-Yeop Kim Chan-Wook Shim Dusun Hwang Yungjoo Chung homogenous over the cross sectional area of the POF. We can calculate the transmission light intensity by determining the area of the light beam passing through the blocker.…”
Section: Formulation Of Transmission Light Intensity Of Hole Blockersmentioning
confidence: 99%
“…Compared with conventional electrical strain gages, fiber optic strain sensors have many advantages, such as electro-magnetic immunity and resistance to chemical corrosion. Therefore, in the past few years, there has been intense works on the development of fiber optic strain sensors [1][2][3][4]. These most of the developed sensors are very sensitive in measuring strain.…”
Section: Introductionmentioning
confidence: 99%
“…A number of high-resolution FBG strain sensors based on complex structures have been developed, including Fabry-Perot configuration [8,9], π-phase shifted gratings [10,11] chirped gratings [12], and sampled structures [13]. For instance, Gagliardi et al demonstrated a strain measurement at the 10 −13 ε·Hz −1/2 scale using an FBG resonator with a diode-laser source which is stabilized against quartz-disciplined optical frequency comb [1]; Huang et al proposed a static-strain sensor with a resolution of 1.0 nε based on a π-phase-shifted Bragg grating, combined with a wavelet threshold denoising algorithm [11].…”
Section: Introductionmentioning
confidence: 99%